Chylous Fistula Following Mastectomy (Journal of Enam Medical College, 2021)
Though chyle leakage after axillary dissection is a rare occurrence, sometimes it becomes difficult to manage. All surgeons dealing with breast should be aware with this unusual complication and its management.J Enam Med Col 2021; 11(2): 133-134